2019
DOI: 10.14238/pi59.3.2019.113-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GeneXpert MTB to Mycobacterium tuberculosis culture in children with tuberculosis

Abstract: Background Diagnosing tuberculosis (TB) in children is difficult. Typical methods take a long time to achieve results, or have a low sensitivity. GeneXpert is a nucleic acid amplification test used to identify Mycobacterium tuberculosis bacteria (MTB) in only 2 hours. Objective To compare the sensitivity and specificity of GeneXpert MTB to MTB culture in children with TB, and to assess factors associated with GeneXpert MTB test in predicting which children were likely to have positive results. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…15,16 Notably, other studies have suggested that individuals aged 10 to 18 years are most strongly correlated with positive GeneXpert® MTB results. 17 DM emerged as the most prevalent comorbidity in our study. DM-TB patients with elevated and uncontrolled blood sugar levels face compromised immune systems, escalating the risk of TB treatment failure, severe complications, and a heightened mortality risk compared to those without comorbidities.…”
Section: Subject Characteristics and Research Resultsmentioning
confidence: 55%
“…15,16 Notably, other studies have suggested that individuals aged 10 to 18 years are most strongly correlated with positive GeneXpert® MTB results. 17 DM emerged as the most prevalent comorbidity in our study. DM-TB patients with elevated and uncontrolled blood sugar levels face compromised immune systems, escalating the risk of TB treatment failure, severe complications, and a heightened mortality risk compared to those without comorbidities.…”
Section: Subject Characteristics and Research Resultsmentioning
confidence: 55%
“… 21 In contrast to the findings of this study, a report in Indonesia found that gender and age group were factors related to MTB detection. 22 Despite the adoption of the Xpert MTB/RIF test as the first line diagnostic, the poor detection rate for MTB may reflect the difficulty in diagnosing childhood TB. This also calls for greater study into the development of better diagnostic methods to improve case detection and prompt treatment for both drug-sensitive and drug-resistant tuberculosis in children.…”
Section: Discussionmentioning
confidence: 99%